Struktur Histologis Insang dan Kadar Hemoglobin Ikan Asang (Osteochilus hasseltii C.V) di Danau Singkarak dan Maninjau, Sumatera Barat - Hari Marta Saputra; Netti Marusin; Putra Santoso (Jurnal Biologi Universitas Andalas, 2013)
A study on histological structure of gill and hemoglobin concentration of Silver Sharkminnow (Osteochilus hassletii C.V) in Singkarak and Maninjau Lakes, West Sumatera has been conducted from December 2012 to March 2013. This study aimed to determine the damage of histological structure of gill and haemoglobin concentration of O. hasseltii. We prepared slide preparation of gills to observe their damage structure, while hemoglobin concentration was counted/measured using Sahli method. The results showed various types of damage such as edema, loss of the epithelium on the secondary lamella, hyperplasia, fusion of secondary lamella, the loss of the secondary lamella structure, clubbing and thickening of elastic cartilage. Hemoglobin concentration of O. hasseltii ware 3.28% and 3.05 % for Singkarak and Maninjau respectively. There was no statistically significant difference between sampling sites for both of studied parameters.Keywords: Ostechilius hasseltii, gill histology, hemoglobin, Singkarak and Maninjau lakes